2006
DOI: 10.1111/j.1600-0609.2006.00809.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T‐cell phenotype in association with large cell transformation of mycosis fungoides

Abstract: Transformation of MF to high grade lymphoma may be associated with the adoption of a regulatory T-cell phenotype. FOXP3 expression may contribute to aggressive behavior of MF after large cell transformation via immune escape mechanism. The significance of this observation is limited by the low case number in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 10 publications
(11 reference statements)
2
29
1
Order By: Relevance
“…This finding agrees with other published studies that indicate that FoxP3 protein is not expressed to any significant degree by neoplastic cells in skin lesions or peripheral blood of most patients with MF/SS whereas the cutaneous infiltrates do have variable proportions of tumor-infiltrating FoxP3+ cells [62][63][64][65]. In recent study, Gjerdrum evaluated FoxP3 protein expression in 69 patients with MF further classified into early patch/plaque (n = 10), infiltrated plaque (n = 42), non-transformed tumor (n = 10), and transformed tumor (n = 7) cases [65].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding agrees with other published studies that indicate that FoxP3 protein is not expressed to any significant degree by neoplastic cells in skin lesions or peripheral blood of most patients with MF/SS whereas the cutaneous infiltrates do have variable proportions of tumor-infiltrating FoxP3+ cells [62][63][64][65]. In recent study, Gjerdrum evaluated FoxP3 protein expression in 69 patients with MF further classified into early patch/plaque (n = 10), infiltrated plaque (n = 42), non-transformed tumor (n = 10), and transformed tumor (n = 7) cases [65].…”
Section: Discussionsupporting
confidence: 93%
“…This study also found that FoxP3 protein was not expressed by neoplastic cells in the skin infiltrate in any of these cases although it should be noted that negative FoxP3 staining was defined as absent or less than 10% staining by neoplastic cells, suggesting that occasional neoplastic cells could have been positive. Interestingly, the lack of FoxP3 protein in transformed MF in this study differs from the experience of Hallermann in which 4 of 5 cases of CD30+ transformed MF cases expressed FoxP3 [64]. The reason for this discrepancy is unclear but could be due to technical reasons (immunohistochemistry with or without antigen retrieval; FoxP3 antibody clones 236A/E7 versus hFoxy) [66].…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…[35][36][37][38][39] One recent study has indicated that transformation of MF to CD30-positive large T-cell lymphomas is associated with a Treg phenotype. 40 However, the limited number of cases investigated (n ¼ 5) and the lack of controls for the immunolabelling restricts the interpretation of this study.…”
Section: Discussionmentioning
confidence: 94%
“…[52][53][54] Similarly, a study using the controversial hFOXY anti-FOXP3 antibody found that four patients with non-transformed MF were FOXP3-negative but that the malignant T cells in four of five patients with transformed MF expressed FOXP3 indicating that transformation of MF to a high-grade lymphoma is associated with adoption of a Treg phenotype. 55 However, FOXP3 þ malignant T cells were not detected when sections from the same patients were subsequently stained with three distinct FOXP3-specific antibodies. 56 In a larger study, Gjerdrum et al 57 did observe a sub-population of FOXP3 þ malignant T cells in 6 of 86 patients with CTCL of which 69 had MF and 17 CTCL unspecified.…”
Section: Tregs In Mfmentioning
confidence: 99%